Membrane lipid modifications and therapeutic effects mediated by hydroxydocosahexaenoic acid on Alzheimer's disease - Torres, M; Price, SL; Fiol-deRoque, MA; Marcilla-Etxenike, A; Ahyayauch, H; Barceló-Coblijn, G; Terés, S; Katsouri, L; Ordinas, M; López, DJ; Ibarguren, M; Goñi, FM; et al. (Elsevier, 2013)
Alzheimer's disease (AD) is a neurodegenerative pathology with relevant unmet therapeutic needs. Both natural aging and AD have been associated with a significant decline in the omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA), and accordingly, administration of DHA has been proposed as a possible treatment for this pathology. However, recent clinical trials in mild-to-moderately affected patients have been inconclusive regarding the real efficacy of DHA in halting this disease. Here, we show that the novel hydroxyl-derivative of DHA (2-hydroxydocosahexaenoic acid - OHDHA) has a strong therapeutic potential to treat AD. We demonstrate that OHDHA administration increases DHA levels in the brain of a transgenic mouse model of AD (5xFAD), as well as those of phosphatidylethanolamine (PE) species that carry long polyunsaturated fatty acids (PUFAs). In 5xFAD mice, administration of OHDHA induced lipid modifications that were paralleled with a reduction in amyloid-β (Αβ) accumulation and full recovery of cognitive scores. OHDHA administration also reduced Aβ levels in cellular models of AD, in association with alterations in the subcellular distribution of secretases and reduced Aβ-induced tau protein phosphorylation as well. Furthermore, OHDHA enhanced the survival of neuron-like differentiated cells exposed to different insults, such as oligomeric Aβ and NMDA-mediated neurotoxicity. These results were supported by model membrane studies in which incorporation of OHDHA into lipid-raft-like vesicles was shown to reduce the binding affinity of oligomeric and fibrillar Aβ to membranes. Finally, the OHDHA concentrations used here did not produce relevant toxicity in zebrafish embryos in vivo. In conclusion, we demonstrate the pleitropic effects of OHDHA that might prove beneficial to treat AD, which suggests that an upstream event, probably the modulation of the membrane lipid composition and structure, influences cellular homeostasis reversing the neurodegenerative process. This Article is Part of a Special Issue Entitled: Membrane Structure and Function: Relevance in the Cell's Physiology, Pathology and Therapy.